Strategi Pemasaran Produk Gadai Syariah Dan Pengaruhnya Terhadap Minat Nasabah PT. BPR Syariah Bangka Belitung Cabang Pangkalpinang - Sumar Sumar; Dony Yanuar (Holistic Journal of Management Research, 2015)
This study aims to determine how the marketing strategy of PT BPRS Bangka Belitung Pangkalpinang branch in attracting customers and assess how much influence the product strategy, pricing strategy, promotion strategy and the strategy of the client's interest PT BPR Syariah Bangka Belitung Branch Pangkalpinang either partially or simultaneously. This research uses descriptive and quantitative research. The sampling method in this study is the type of nonprobability sampling system used random sampling. The population in this study were 198 customers who conduct transactions at islamic pawn PT BPRS Babel Pangkalpinang branch. The samples by using Slovin formula with an error level of 5% obtained a sample of 132 people. Methods of data analysis using descriptive statistics, test validity, reliability test, the classic assumption test, t test, F test, regression test, and the coefficient of determination (R2). The results showed partial variable positive influence product strategy by 7.6% but not significant by t-test result of 1.004 <1.66 level of significance and the t table 0.317> 0.05 against the interests of customers, a variable pricing strategy has positive effect by 50% and significant by t test of 4.366> 1.66 t table and a significance level of 0.00 <0.05 on customers' interest, variable promotion strategies have positive influence by 21.8% and significant by t test of 2.935>1.66 t table and a significance level of 0.004 <0.05 on customers' interest. variable place strategies have positive influence by 27% and significant by t test of 2.382> 1.66 t table and a significance level of 0.019 <0.05 on customers' interest. Simultaneously variable product strategy, pricing strategy, promotion strategy and the strategy of positive and significant impact on consumer loyalty to the F test results for 15,180> 3,91 F table with a significance level of 0.00 <0.05. Adjusted R square value of 0.302 means that 30.2% of customers interest can be explained or influenced by variable product strategy, pricing strategy, promotion strategy and a strategy, while the remaining 69.2% interest in customers is influenced by other variables not examined in this research.